1997
DOI: 10.1210/endo.138.6.5199
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphorylation Influences Adhesive Junction Assembly and Follicular Organization of Cultured Thyroid Epithelial Cells*

Abstract: The follicular histoarchitecture of the thyroid forms the anatomical basis for thyroid physiology and is commonly disturbed in diseases of the thyroid. We have used cultured porcine thyroid cells to study thyroid epithelial morphogenesis and its regulation. When cultured in the presence of TSH, freshly isolated thyroid cells reorganize to form follicles within three-dimensional cell aggregates. However, when established follicles are washed into TSH-free medium, thyroid cells spread and migrate to convert foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The SFK family was thought to be required for epithelial TJ dynamics (Yap et al , 1997; Tsukamoto and Nigam, 1999; Meyer et al , 2001; Chen et al , 2002). The bidirectional interaction of EGFR and SFKs generates a synergistic cellular signaling event for promoting a variety of cell actions, as well as cell transformation in pathological conditions (Ishizawar and Parsons, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SFK family was thought to be required for epithelial TJ dynamics (Yap et al , 1997; Tsukamoto and Nigam, 1999; Meyer et al , 2001; Chen et al , 2002). The bidirectional interaction of EGFR and SFKs generates a synergistic cellular signaling event for promoting a variety of cell actions, as well as cell transformation in pathological conditions (Ishizawar and Parsons, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The association of EGFR and SFKs results in the activation of SFKs. Meanwhile, SFK is likely to phosphorylate its downstream targets, such as Par3, possibly also occludin and ZO‐1 (Yap et al , 1997; Tsukamoto and Nigam, 1999; Chen et al , 2002), which may modify TJ protein activity thereby regulating TJ formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diminished E-cadherin expression has been pro- posed as a factor dictating the characteristic growth pattern of diffuse gastric carcinoma [32] on the basis of aberrant tyrosine kinase activity and resultant alteration in cell adhesion properties [33]. In the case of PTCret+ it is possible that both these factors act synergistically, though this begs the question of why PTCrettumors should be morphologically indistinguishable.…”
Section: Discussionmentioning
confidence: 99%
“…have demonstrated alterations in the nuclear envelope and chromatin structure in primary culture of thyroid cells infected with a retroviral vector expressing activated RET/PTC‐1 and it is possible that ret /PTC‐1 activation may influence the growth pattern in PTC, firstly because failure to express the putative cytoskeletal protein H4 alters the structure of the cell, or secondly, because RET/PTC‐1 is constitutively phosphorylated. Yap et al 21. have shown that increased tyrosine phosphorylation alters thyroid epithelial organization in culture by altering the assembly of actin‐associated adhesive junctions.…”
Section: Discussionmentioning
confidence: 99%